Function of Aizuchi in The Podcast as One of Digital Communication Media - Salsabila Putri Perdana; Hety Nurohmah (Universitas Diponegoro, 2022)
unintentionally. Because communication is essential, the use of language becomes the main thing for social life. In line with this, the use of language in each nation also has its characteristics. One is in Japan, which has a unique way of communicating, Aizuchi. Aizuchi is a form of response so that the speaker feels heard and understood by the listener. In this era of globalization, when technology is increasingly sophisticated, it is also easier for humans to communicate through podcast media as one of the audiovisual media that can be listened to anywhere and anytime because the platform for listening or watching it is straightforward to access. This study's data source was taken from the Yuyu no Sekai Podcast in the episode